The effect of the COVID-19 pandemic on the mental status of health workers at sports clubs - Denerel, Nevzad; Öçal, Onur Yüksel (My University, 2023)
Objective: COVID-19 pandemic has affected many people as well as athletes and healthcare professionals mentally. Although there are many studies examining the effect of the pandemic on the mental status of athletes and hospital staff, its effect on the psychological status of professionals providing athlete health care is unknown. This study investigates the effect of the pandemic on the mental health status of health workers of employed in sports clubs. Method: A total of 192 physicians, physiotherapists and masseurs employed in four different sports branches (football, basketball, volleyball, handball) participated in this survey study, which was conducted one year after the outbreak of the pandemic. Three questionnaires, including Depression Anxiety Stress Scale-21 (DASS-21), Coronavirus Anxiety Scale, and Coronavirus Fear Scale were administered to evaluate the mental status of the participants. Results: Physiotherapists' DASS-21 total and stress subgroup scores were found to be higher than those of masseurs (p=0.013, p=0.016, respectively). When compared by sports branches, the measurement results of healthcare professionals were similar (p>0.05). The DASS-21 anxiety subgroup scores were found to be higher in those who had COVID-19 infection than in those who did not (p=0.004). Nevertheless, the mean scores of the participants were in the normal range. Conclusion: In this study, which was conducted about a year after the beginning of the pandemic, the COVID-19 pandemic and the coronavirus infection did not have a significant effect on the mental state of the sports health workers. This can be attributed to the fact that healthcare professionals have adapted to the pandemic process.
Keywords: COVID-19; mental health; team sports; health team